2015
DOI: 10.7863/ultra.34.6.993
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience With the New York State Breast Density Inform Law at a Community‐Based Breast Center

Abstract: ammography is the only method of screening that has been shown to reduce breast cancer mortality, with a reduction of approximately 30%. 1 However, the limitations of mammography are well known and include the reduced sensitivity in dense breast tissue, which can be as low as 30% to 48%. 2,3 Detecting cancer in dense breasts has been a challenge to breast imagers; it is an important challenge to overcome, as women with dense breast tissue make up approximately half of the population in women younger than 50 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
0
14
0
2
Order By: Relevance
“…A previous study in our clinic found a 2% uptake of supplemental screening ultrasound for women notified of their dense breast tissue in an initial period after implementation of the law in our state (NY) [110]. Further review of our patient population has showed a steady increase in adoption.…”
Section: The Current Clinical Landscape Of Mbdmentioning
confidence: 81%
“…A previous study in our clinic found a 2% uptake of supplemental screening ultrasound for women notified of their dense breast tissue in an initial period after implementation of the law in our state (NY) [110]. Further review of our patient population has showed a steady increase in adoption.…”
Section: The Current Clinical Landscape Of Mbdmentioning
confidence: 81%
“…Data show that breast ultrasound identifies additional breast cancers that have been missed by mammograms among women with dense breasts [1923], and the application of automated whole breast ultrasound imaging [2426] makes it feasible that this modality may one day be introduced as a screening tool for women with dense breasts. Consequently, it is worthwhile to understand how making women aware of this technology will influence their decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…We noted that the time between screening mammography and screening sonography decreased, as in this study, we found an average of 24 days, with 71% (3881) on the same day. Our prior report found an average of 65 days, with most (87%) performed on a different day . This finding was likely due to our recall protocol for these patients.…”
Section: Discussionmentioning
confidence: 78%
“…Patients are notified at the time of screening mammography of their breast density. Methods of notification at our facility, as well as standard‐of‐care procedures, have been previously reported …”
Section: Methodsmentioning
confidence: 99%